2012
DOI: 10.1121/1.4757732
|View full text |Cite
|
Sign up to set email alerts
|

Annoyance and self-reported sleep disturbance due to night-time railway noise examined in the field

Abstract: Railway noise interferes with daytime activities and disturbs sleep leading to annoyance of exposed residents. The main objective of this paper was to establish exposure-response relationships between nocturnal railway noise exposure and annoyance and to examine self-reported sleep disturbances as short-term reactions to noise. In a field study 33 residents living close to railway tracks in the Cologne/Bonn area (Germany) were investigated. Railway noise was measured indoors during nine consecutive nights at e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 31 publications
3
22
0
Order By: Relevance
“…The noise events in the night are dominated by freight train traffic which has been shown to be more annoying than passenger train traffic. [7,9,59] The data support the penalties applied to the night and evening before combining noise levels to the energy equivalent noise index L den and even higher penalty for the evening than applied at present, since no significant differences between the night-time and evening period were found.…”
Section: (○) Latent Variable (□) Observed Variablesupporting
confidence: 52%
“…The noise events in the night are dominated by freight train traffic which has been shown to be more annoying than passenger train traffic. [7,9,59] The data support the penalties applied to the night and evening before combining noise levels to the energy equivalent noise index L den and even higher penalty for the evening than applied at present, since no significant differences between the night-time and evening period were found.…”
Section: (○) Latent Variable (□) Observed Variablesupporting
confidence: 52%
“…This question is of high environmental importance, especially as there is an expected increase in the market share of freight traffic from 8% in 2001 to 15% in 2020 [5]. To contextualise the potential problem, recent field studies have observed between 3–19 nightly freight pass-bys in Norway [6] and up to 150 during bedtime in Germany [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, the time constant used for averaging in the calculations of the noise level seems to have a relevant effect on the annoyance, as recently shown in a study on nighttime annoyance and sleep disturbance (Pennig et al, 2012). In that study, the L Aeq averaged over the night did not correlate with the reported annoyance or sleep disturbance of that night when controlling for nonacoustical factors; however, the number of trains, and in particular, the number of freight trains did.…”
Section: Implications For Long-term Annoyancementioning
confidence: 81%